(untitled) (Archaeologia Adriatica, 2008)
The article analyzes the fragments of three glass cups signed by Ennion, discovered during excavation of the Roman amphitheater in Burnum. A fragment of yellowish glass with the letters ...O / ...Ω in the tabula and a fluted pattern in the lower part belonged to the first example. The find corresponds to type Harden A1i, and analogies can be found in examples from Narona, Tremithusa on Cyprus, and Cavarzera u Italiji. The second example consists of five opieces of cobalt blue glass, with a floral decoration of grapevine tendrils and grape bunches, and the left side of the tabula ansata with the remains of the inscription ENN… / EΠO… / CE… It corresponds typologically to variant Harden A2i, and analogies can be found in examples from Cavarzera, Bagnola near Brescia, and the Metropolitan Museum. The third example consists of four fragments of yellowish glass with channelling, which could belong to a cup of type Harden A2iv. All three Burnum examples come from archaeological levels, dated within the chronological period from Tiberius to Claudius, created by filling fissures in the rocks during leveling the terrain for construction of the amphitheater. Considering that Burnum in this period was the seat of the XI legion and auxiliary military units (Alae I Hispanorum and Cohortis II Cyrrhestarum sagittariae), such luxurious objects could have belonged to high-ranking military officers of the units. Along with finds from Narona and Tilurium, Burnum is the third site in Dalmatia where Ennion cups have been found, making it, next to northern Italy, the region with the greatest number of discovered examples. Nonetheless, this does not solve the question about the site of production (the Syrian-Palestinian area or northern Italy – Aquileia), or the region of delivery of Ennion products, as the frequently traveled eastern coast of the Adriatic with its centers (Narona, Salona, Scardona, Iader, etc.), was in intensive trade connections with both of the above areas.